Nanoparticle drug delivery systems for cancer treatment - Gali-Muhtasib, Hala; Chouaib, Racha (Milton : Pan Stanford Publishing, 2020)
In recent years, nanoparticles--bionanomaterials with specific physicochemical properties--have gained a great deal of scientific interest owing to their unique structure. Nanoparticle-based drugs are now widely regarded as a safer, more precise, and more effective mode of cancer therapy, considering their ability to enhance drug bioavailability, improve site-specific drug delivery, and protect nontarget tissues from toxic therapeutic drugs. This book compiles and details cutting-edge research in nanomedicine from an interdisciplinary team of international cancer researchers who are currently revolutionizing drug delivery techniques through the development of nanomedicines and nanotheranostics. Edited by Hala Gali-Muhtasib and Racha Chouaib, two prominent cancer researchers, this book will appeal to anyone involved in nanotechnology, cancer therapy, or drug delivery research.
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: Cancer -- Chemotherapy; Drug delivery systems; Nanomedicine; MEDICAL / Biotechnology; MEDICAL / Oncology; SCIENCE / Biotechnology